Use of electronic healthcare records to identify complex patients with atrial fibrillation for targeted intervention. (3rd July 2016) - Wang, Shirley V; Rogers, James R; Jin, Yinzhu; Bates, David W; Fischer, Michael A
Abstract : Background: Practice guidelines recommend anticoagulation therapy for patients with atrial fibrillation (AF) who have other risk factors putting them at an elevated risk of stroke. These patients remain undertreated, but, with increasing use of electronic healthcare records (EHRs), it may be possible to identify candidates for treatment. Objective: To test algorithms for identifying AF patients who also have known risk factors for stroke and major bleeding using EHR data. Materials and Methods: We evaluated the performance of algorithms using EHR data from the Partners Healthcare System at identifying AF patients and 16 additional conditions that are risk factors in the CHA2 DS2 -VASc and HAS-BLED risk scores for stroke and major bleeding. Algorithms were based on information contained in problem lists, billing codes, laboratory data, prescription data, vital status, and clinical notes. The performance of candidate algorithms in 1000 bootstrap resamples was compared to a gold standard of manual chart review by experienced resident physicians. Results : Physicians reviewed 480 patient charts. For 11 conditions, the median positive predictive value (PPV) of the EHR-derived algorithms was greater than 0.90. Although the PPV for some risk factors was poor, the median PPV for identifying patients with a CHA2 DS2 -VASc score ≥2 or a HAS-BLED score ≥3 was 1.00 and 0.92, respectively. Discussion: We developed and tested a set of algorithms to identify AF patients and known risk factors for stroke and major bleeding using EHR data. Algorithms such as these can be built into EHR systems to facilitate informed decision making and help shift population health management efforts towards patients with the greatest need.